Development of an instructional package for enhancing e-safety awareness among secondary school students in Kerala, India - Vasudevan, Asokan; John, Sojia; Raja, N.; Krishnasamy, Hariharan N; Parahakaran, Suma; Prasad, Rabindra Dev Prasad (Edelweiss Applied Science and Technology, 2025)
The increasing early exposure of children to the internet, involving activities such as social networking, gaming, and shopping, has raised concerns about their vulnerability to cybercrimes. Children, particularly secondary school students in Kerala, are at significant risk due to their lack of understanding of online risks and safety measures. This has led to challenges for schools, as the rise in cyber threats poses severe national and social security risks. To address this, a study evaluated the effectiveness of an instructional package called 'e-SHIELD' in enhancing e-safety awareness among 90 secondary school students in Kerala. The experimental treatment involved pre- and post-tests to measure the impact of the instructional package on students' awareness of e-safety. The results demonstrated a significant improvement in e-safety awareness among students after the package's implementation, with no significant difference between male and female students. The study underscores educators' crucial and valued role in teaching students how to use technology safely, emphasizing the need for ongoing education to ensure proactive internet safety throughout their lives.